2006
DOI: 10.1136/jmg.2006.044149
|View full text |Cite
|
Sign up to set email alerts
|

Methylation analysis of KvDMR1 in human oocytes

Abstract: Recently, several reports have been published that showed a higher incidence of assisted reproductive technologies (ART) in patients with Beckwith-Wiedemann syndrome compared with the general population, and in most of these patients, aberrant methylation imprints of KvDMR1 have been found. This has led to the concern that ART might increase the incidence of imprinting syndromes such as Beckwith-Wiedemann syndrome. Not much is known on environmental or genetic factors that may interfere with the processes of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 23 publications
1
39
1
1
Order By: Relevance
“…KCNQ1OT1 LOM was also observed in 5/23 and 2/37 DNA strands from IVM MII oocyte pools (Khoueiry et al 2008. This contrasts with short-term IVM MII oocytes that had normal SNRPN (three single oocytes), KCNQ1OT1 (four single oocytes), and MEG3 (GTL2) (three pools of two oocytes) methylation (Geuns et al 2003(Geuns et al , 2007a(Geuns et al , 2007b. In the above studies, where zona pellucidae were not removed, there is the possibility of cumulus cell contamination.…”
Section: In Vitro Oocyte Maturationmentioning
confidence: 42%
“…KCNQ1OT1 LOM was also observed in 5/23 and 2/37 DNA strands from IVM MII oocyte pools (Khoueiry et al 2008. This contrasts with short-term IVM MII oocytes that had normal SNRPN (three single oocytes), KCNQ1OT1 (four single oocytes), and MEG3 (GTL2) (three pools of two oocytes) methylation (Geuns et al 2003(Geuns et al , 2007a(Geuns et al , 2007b. In the above studies, where zona pellucidae were not removed, there is the possibility of cumulus cell contamination.…”
Section: In Vitro Oocyte Maturationmentioning
confidence: 42%
“…The development of the single-cell PCR for the IG-DMR was complex, and a rather low amplification efficiency (17.6%) was obtained, compared to similar protocols developed for the SNRPN-gene (28.7%) and the LIT1-gene (25.0%). 18,24 This was most probably due to the numerous tandem repeats present in the sequence of the IG-DMR.…”
Section: Discussionmentioning
confidence: 99%
“…It is assu med that maternal hypomethylation syndrome, in which LOM occurs at multiple maternal loci, may be due to a lack of maternal DNMT3L or DNMT1, although mutation of theses genes is not detected in all patients [17]. In various cases, it is proposed that fertilized eggs derived from epigenetically mutated gametes could contribute to LOI/LOM regardless of whether conception occurs naturally or by ART [13,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators suggest that LOI/LOM could be attributed to assisted reproductive technology (ART) [10][11][12]. On the other hand, Geuns et al showed that 1 out of 16 human oocytes does not possess a KCNQ1OT1 methylation imprint [13]. We also report that the size-dependent acquisition of maternal methylation imprints is recognized in growing oocytes collected from adult mice as in juveniles; however, the hypomethylated alleles in the growing oocytes derived from adults are detected more remarkably than those of juveniles [7].…”
mentioning
confidence: 99%